PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA PERUSAHAAN MELALUI PERILAKU PRODUKTIF KARYAWAN PADA PT. TOMORROW’S ANTIQUES INDONESIA - I Wayan Suartina; Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Luh Sri Astiti (Widya Manajemen, 2019)
This study aims to determine the effect of Total Quality Management (TQM) on employee productive behavior and company performance at PT. Tomorrow’s Antiques Indonesia. This study uses a quantitative method with a sample of 104 employees. Data was collected by observation, interviews, documentation, literature, and questionnaires. The analysis technique used descriptive analysis, path analysis (analysis path), and sobell test. The results of the total quality management (TQM) research have a positive and significant effect on employee productive behaviour at PT. Tomorrow's Antiques with coefficient of 0.986 and a sig value of 0.00 <0.05; employee productive behavior has a positive and significant effect on company performance at PT. Tomorrow's Antiques with coefficient of 0.606 and a sig value of 0.00 <0.05; total quality management (TQM) has a positive and significant effect on company performance at PT. Tomorrow's Antiques with coefficient of 0.396 and a sig value of 0.00 <0.05, and employee productive behaviour can mediate the effect of total quality management (TQM) on company performance at PT. Tomorrow's Antiques with Z value (17,311) > Z table (1,96).